Connecting accounting and communication: A survey of accounting students throughout universities in Malaysia (UiTM, UUM, UPM & UKM) / Halil Paino - Paino, Halil (Universiti Teknologi MARA Cawangan Pahang, 2001)
Communication skills are valued highly in public accounting firms, where all professionals at all levels communicate as part of their jobs. However, respondents to a 2000 survey reported that the development of effective communication skills was not part of their formal accounting education and that partners and managers want their entry-level professionals to have these skills onset. Further these skill increase in importance as accounting professionals progress from the entry-level to manager and to partner. Educational institutions need to develop program that include communication topics and courses to prepare accountants for the challenges of their profession.